Empowering network operating systems with memory management techniques - Doriguzzi-Corin, Roberto; Siracusa, Domenico; Salvador, Elio; Schwabe, Arne (NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium)

Delayed (de-)activation in servers with a sleep mode - Herlich, Matthias; Bredenbals, Nico; Karl, Holger (Sustainable Computing: Informatics and Systems)

SmarterPhones: Anticipatory Download Scheduling for Wireless Video Streaming - Dräxler, Martin; Blobel, Johannes; Dreimann, Philipp; Valentin, Stefan; Karl, Holger (Proceedings of the 2nd International Conference on Networked Systems (NetSys))
Video streaming is in high demand by mobile users. In cellular networks, however, the unreliable wireless channel leads to two major problems. Poor channel states degrade video quality and interrupt the playback when a user cannot sufficiently fill its local playout buffer: buffer underruns occur. In contrast, good channel conditions cause common greedy buffering schemes to buffer too much data. Such over-buffering wastes expensive wireless channel capacity. Assuming that we can anticipate future data rates, we plan the quality and download time of video segments ahead. This anticipatory download scheduling avoids buffer underruns by downloading a large number of segments before a drop in available data rate occurs, without wasting wireless capacity by excessive buffering.We developed a practical anticipatory scheduling algorithm for segmented video streaming protocols (e.g., HLS or MPEG DASH). Simulation results and testbed measurements show that our solution essentially eliminates playback interruptions without significantly decreasing video quality.

HybridTE: Traffic Engineering for Very Low-Cost Software-Defined Data-Center Networks - Wette, Philip; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
The size of modern data centers is constantly increasing. As it is not economic to interconnect all machines in the data center using a full-bisection-bandwidth network, techniques have to be developed to increase the efficiency of data-center networks. The Software-Defined Network paradigm opened the door for centralized traffic engineering (TE) in such environments. Up to now, there were already a number of TE proposals for SDN-controlled data centers that all work very well. However, these techniques either use a high amount of flow table entries or a high flow installation rate that overwhelms available switching hardware, or they require custom or very expensive end-of-line equipment to be usable in practice. We present HybridTE, a TE technique that uses (uncertain) information about large flows. Using this extra information, our technique has very low hardware requirements while maintaining better performance than existing TE techniques. This enables us to build very low-cost, high performance data-center networks.

SynRace: Decentralized Load-Adaptive Multi-path Routing without Collecting Statistics - Schwabe, Arne; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
Multi-rooted trees are becoming the norm for modern data-center networks. In these networks, scalable flow routing is challenging owing to vast number of flows. Current approaches either employ a central controller that can have scalability issues or a scalable decentralized algorithm only considering local information. In this paper we present a new decentralized approach to least-congested path routing in software-defined data center networks that has neither of these issues: By duplicating the initial (or SYN) packet of a flow and estimating the data rate of multiple flows in parallel, we exploit TCP’s habit to fill buffers to find the least congested path. We show that our algorithm significantly improves flow completion time without the need for a central controller or specialized hardware.

Optimizing Software-Defined Networks using Application-Layer Knowledge - Wette, Philip

On Network Application representation and controller independence in {SDN - A. Aranda-Gutierrez, Pedro; Karl, Holger; Rojas, Elisa; Leckey, Alec (2015 European Conference on Networks and Communications, EuCNC 2015, Paris, France, June 29 - July 2, 2015)

Error characterization of multi-access point WSNs in an aircraft cabin - Blanckenstein, Johannes; Nardin, Cristina; Klaue, Jirka; Karl, Holger (IEEE International Conference on Communication, ICC 2015, London, United Kingdom, June 8-12, 2015, Workshop Proceedings)

Topology model to generate realistic latency for simulations - Schwabe, Arne; Karl, Holger (2015 IEEE International Conference on Communications, ICC 2015, London, United Kingdom, June 8-12, 2015)

Anticipatory Download Scheduling in Wireless Video Streaming with Uncertain Data Rate Prediction - Dräxler, Martin; Blobel, Johannes; Karl, Holger (8th IFIP Wireless and Mobile Networking Conference, WMNC 2015, Munich, Germany, October 5-7, 2015)